Sustainable Strategies for Wine Colloidal Stability: Innovations in Potassium Bitartrate Crystallization Control - Zhang, Yuhan (Crystals (Basel), 2025)
Potassium bitartrate (KHT) crystallization, as the dominant factor compromising wine colloidal stability, necessitates advanced control strategies beyond conventional thermodynamic approaches. The formation of tartrate crystals is influenced by various factors, including temperature, pH, and the concentration of tartrate salts. Traditional methods of tartrate stabilization, such as cold stabilization and ion-exchange resins, while effective, are associated with high energy consumption and significant environmental impact. In recent years, with the growing emphasis on green and sustainable development, researchers have begun exploring more environmentally friendly innovative technologies. This review examines the factors affecting tartrate crystallization and their implications for wine quality, detailing traditional stabilization techniques as well as newer methods involving protective colloids and stabilizers. Special attention is given to recent advancements in green technologies, such as plasma surface modification, the use of zeolites as wine processing aids, and the synergistic application of algal polysaccharides. Finally, the paper outlines future directions for tartrate stabilization technology, underscoring the importance of green and sustainable practices in the wine industry.